Dietary monoterpenoids and human health: Unlocking the potential for therapeutic use - Vyhlídalová, Barbora; Ondrová, Karolína; Zůvalová, Iveta (Biochimie, 2025)
Natural products are widely used in different aspects of our lives - from household cleaners and food production, via cosmetics and aromatherapy, to both alternative and traditional medicine. In our research group, we have recently described several monoterpenoids with potential in the antiviral and anticancer therapy by allosteric targeting of aryl hydrocarbon receptor (AhR). Prior to any practical application, biological effects on human organism must be taken in concern. This review article is focused on the biological effects of 5 monoterpenoids on the human health previously identified as AhR antagonists with a therapeutic potential as antiviral and anticancer agents. We have thoroughly described cytotoxic, anti-inflammatory, anti-proliferative, and anticancer effects, as well as known interactions with nuclear receptors. As clearly demonstrated, monoterpenoids in general represent almost an inexhaustible reservoir of natural compounds possessing the ability to influence, modulate and improve human health.
Keywords: Neoplasms; nádory; Antiviral Agents; monoterpeny; lidé; receptory aromatických uhlovodíků; Receptors, Aryl Hydrocarbon; Antineoplastic Agents; protinádorové látky; Monoterpenes; antivirové látky; Humans